Targeted Deletion of the Claudin12 Gene in Mice Increases Articular Cartilage and Inhibits Chondrocyte Differentiation - Xing, Weirong; Pourteymoor, Sheila; Chen, Yian; Mohan, Subburaman (Frontiers in Endocrinology, 2022)
To study the role of Claudin (CLDN)12 in bone, we developed mice with a targeted deletion of exon2 in the Cldn12 gene for skeletal phenotype analysis. Micro-CT analysis of the secondary spongiosa of distal femurs of mice with targeted disruption of the Cldn12 gene and control lit-termates showed no significant genotype-specific differences in either cortical or trabecular bone parameters for either gender in 13-week-old mice. Immunohistochemistry revealed that while CLDN12 was expressed in both differentiating chondrocytes and osteoblasts of the secondary spongiosa of 3-week-old wild-type mice, its expression was restricted to differentiating chon-drocytes in the articular cartilage and growth plate in adult mice. Articular cartilage area at the knee were increased by 47% in Cldn12 knockout (KO) mice compared to control littermates. Mi-cro-CT analyses found that while the trabecular number was increased by 9% and the trabecular spacing was reduced by 9% in the femoral epiphysis of Cldn12 KO mice, neither bone volume nor bone volume adjusted for tissue volume was different between the two genotypes. The expression levels of Clusterin, Lubricin and Mmp13 were increased by 56%, 46%, and 129%, respectively, in primary articular chondrocytes derived from KO compared to control mice. Our data indicate that targeted deletion of the Cldn12 gene in mice increases articular cartilage and trabecular bone formation of the epiphyses but inhibits chondrocyte differentiation.